Assessing the effectiveness of Enhanced Psychological Care for patients with depressive symptoms attending cardiac rehabilitation compared with treatment as usual (CADENCE): a pilot cluster randomised controlled trial - Suzanne H. Richards (Trials, 2018)
Abstract Background Around 17% of people attending UK cardiac rehabilitation programmes have depression. Optimising psychological wellbeing is a rehabilitation goal, but provision of psychological care is limited. We developed and piloted an Enhanced Psychological Care (EPC) intervention embedded within cardiac rehabilitation, aiming to test key areas of uncertainty to inform the design of a definitive randomised controlled trial (RCT) and economic evaluation. Methods An external pilot randomised controlled trial (RCT) randomised eight cardiac rehabilitation teams (clusters) to either usual care of cardiac rehabilitation provision (UC), or EPC in addition to UC. EPC comprised mental health care coordination and patient-led behavioural activation with nurse support. Adults eligible for cardiac rehabilitation following an acute coronary syndrome and identified with new-onset depressive symptoms during an initial nurse assessment were eligible. Measures were performed at baseline and 5- and 8-month follow-ups and compared between EPC and UC. Team and participant recruitment and retention rates, and participant outcomes (clinical events, depression, anxiety, health-related quality of life, patient experiences, and resource use) were assessed. Results Eight out of twenty teams were recruited and randomised. Of 614 patients screened, 55 were eligible and 29 took part (5%, 95% CI 3 to 7% of those screened), with 15 patient participants cluster randomised to EPC and 14 to UC. Nurse records revealed that 8/15 participants received the maximum number of EPC sessions offered; and 4/15 received no sessions. Seven out of fifteen EPC participants were referred to another NHS psychological service compared to none in UC. We followed up 27/29 participants at 5 months and 17/21 at 8 months. The mean difference (EPC minus UC) in depressive symptoms (Beck Depression Inventory) at follow-up (adjusting for baseline score) was 1.7 (95% CI − 3.8 to 7.3; N = 26) at 5 months and 4.4 (95% CI − 1.4 to 10.2; N = 17) at 8 months. Discussion While valued by patients and nurses, organisational and workload constraints are significant barriers to EPC implementation. There remains a need to develop and test new models of psychological care within cardiac rehabilitation. Our study offers important data to inform the design of future trials of similar interventions. Trial registration ISRCTN34701576. Registered on 29 May 2014. Funding details: UK NIHR HTA Programme (project 12/189/09).